Tracing the World’s Culture in the US Elementary School Students’ Literature - Mulyani, Petra Kristi (Universitas Negeri Semarang, 2019)
Multicultural education was once a new concept in education. Arguments on the content of multicultural education were evolving throughout the history of education. As many countries in the world, the United States experienced challenges in integrating culture into the curriculum. Pros and cons have created different views on providing multicultural education. There were concerns about losing the country identity when considering the diverse cultures into the curriculum. In fact, culturally responsive classroom builds a connection between students and the world. It develops students’ skills to adapt and survive in the diverse and changing world. As we understand the importance of multicultural education, this paper will trace the world’s culture in the US elementary school students’ literature through literature research of several references. The questions raised were: ‘How was the history of multicultural education in the US? How did the history of multicultural education in the US affect the elementary school curriculum? How does the multicultural education affect the elementary school literature? Does elementary school literature contain and reflect the knowledge and values of various world’s cultures? How is the implementation of multicultural education in the elementary school?’ The results of the discussion were based on the combined references used in this research.